Vascular reactivity, chemical profile, toxicological and pharmacokinetic studies of andrographis paniculata nees extracts [RS1-441]. - Raghava Naidu, Sriramaneni (2009)

(untitled)
Tujuan kajian ini adalah untuk menilai reaktiviti vaskular, profil kimia,ketoksikan dan farmakokinetik ekstrak Andrographis paniculata.